2015
DOI: 10.1002/cphc.201500964
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Ni Catalysts Prepared from Amorphous Ni–Zr Alloys: Enhanced Catalytic Performance for Hydrogen Generation from Ammonia Borane

Abstract: Skeletal Ni catalysts were prepared from Ni-Zr alloys, which possess different chemical composition and atomic arrangements, by a combination of thermal treatment and treatment with aqueous HF. Hydrogen generation from ammonia borane over the skeletal Ni catalysts proceeded efficiently, whereas the amorphous Ni-Zr alloy was inactive. Skeletal Ni prepared from amorphous Ni30 Zr70 alloy had a higher catalytic activity than that prepared from amorphous Ni40 Zr60 and Ni50 Zr50 alloys. The atomic arrangement of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Although noble-metal-based catalysts show significant activities for H 2 generation by hydrolysis of AB, practical applications require the development of low-cost metal catalysts. Nanoparticle catalysts based on first-row transition metals, such as Fe, Co, Ni, and Cu have shown high AB hydrolysis activities. ,, As in the case of noble-metal catalysts, supports are critical for the high catalytic performance of non-noble-metal catalysts. Polymers have also been used to stabilize non-noble-metal NPs.…”
Section: Solvolysis Of Abmentioning
confidence: 99%
“…Although noble-metal-based catalysts show significant activities for H 2 generation by hydrolysis of AB, practical applications require the development of low-cost metal catalysts. Nanoparticle catalysts based on first-row transition metals, such as Fe, Co, Ni, and Cu have shown high AB hydrolysis activities. ,, As in the case of noble-metal catalysts, supports are critical for the high catalytic performance of non-noble-metal catalysts. Polymers have also been used to stabilize non-noble-metal NPs.…”
Section: Solvolysis Of Abmentioning
confidence: 99%
“…Recently, we reported that the atomic arrangement of a precursor dramatically affects the structure and catalytic properties of the resultant nanoporous metal catalysts. We found that using an amorphous alloy as the precursor for a nanoporous metal catalyst leads to a finer structure than that formed using the corresponding crystalline alloy owing to the high corrosion resistance of the amorphous alloy. It is expected that CeO 2 with a fine porous structure would be obtained using an amorphous alloy as a precursor as well. Aluminum (Al) has known to be an element which can form amorphous alloy with Ce, albeit within a limited range of composition (7%–10% Ce) and Al can be easily extracted from the alloy by chemical treatment in basic solutions.…”
Section: Introductionmentioning
confidence: 93%